2018
DOI: 10.1186/s12905-018-0605-1
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of obstetric fistula in sub Sahara African countries, from patients’ perspective: a systematic review of qualitative studies

Abstract: BackgroundWomen with fistula live in a state of distress and in fear of their future life. An obstetric fistula has a devastating impact on affected women and their families. The objective of this systematic review was to synthesize the evidence from published articles on the consequences of obstetric fistula on women who endure the condition.MethodsThe consequences were systematically reviewed from purely qualitative and mixed method primary studies. The literatures were searched through the search engines Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 23 publications
2
84
0
Order By: Relevance
“…In another study, escaping sex is called fear of the future lacking a partner, not getting married, and not getting pregnant were among concerns of the patients [11]. Lack of close contact with the husband has been cited as a serious and painful problem [27], and efforts to maintain family and marital relationships have been regarded as an important issue in a systematic review and qualitative meta-synthesis [28]. Women are concerned about the fact that their husband sees them defecating during sexual intercourse [15], which even leads to the fear of divorce and remarriage by the husband [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, escaping sex is called fear of the future lacking a partner, not getting married, and not getting pregnant were among concerns of the patients [11]. Lack of close contact with the husband has been cited as a serious and painful problem [27], and efforts to maintain family and marital relationships have been regarded as an important issue in a systematic review and qualitative meta-synthesis [28]. Women are concerned about the fact that their husband sees them defecating during sexual intercourse [15], which even leads to the fear of divorce and remarriage by the husband [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were in constant fear, and none of the patients in the present study disclosed their disease to non-family members and found it necessary to keep it a secret, which has been confirmed by various studies. This has led to psychological consequences in these patients [11,15,27,28,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of close contact with the husband has been cited as a serious and painful problem [27], and efforts to maintain family and marital relationships have been regarded as an important issue in a systematic review and qualitative meta-synthesis [28]. Women are concerned about the fact that their husband sees them defecating during sexual intercourse [15], which even leads to the fear of divorce and remarriage by the husband [29].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal fistula is a debilitating condition that has pervasive consequences on women's psychological, social, physical and economic wellbeing. Without surgical intervention women with fistula face lifetime embarrassment, isolation, social stigmatization and marital separation [3][4][5]. Furthermore, they are prone to develop chronic vaginal and urinary tract infections, renal failure, pelvic inflammatory disease and amenorrhea [1,6].…”
Section: Introductionmentioning
confidence: 99%